2008
DOI: 10.1159/000151745
|View full text |Cite
|
Sign up to set email alerts
|

Time Lapse Imaging Techniques for Comparison of Mineralization Dynamics in Primary Murine Osteoblasts and the Late Osteoblast/Early Osteocyte-Like Cell Line MLO-A5

Abstract: Mineralization of bone matrix and osteocyte differentiation occur simultaneously and appear interrelated both spatially and temporally. Although these are dynamic events, their study has been limited to using static imaging approaches, either alone or in combination with chemical and biochemical analysis and/or genetic manipulation. Here we describe the application of live cell imaging techniques to study mineralization dynamics in primary osteoblast cultures compared to a late osteoblast/early osteocyte-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…FRFP binding relies on local bone surface area, and removal of tracer probe is reflected in animals undergoing increased bone turnover. Combining fluorescent bisphosphonates with other fluorescent markers of osteoblastic, (72) osteocytic, (73) or osteoclastic (71) markers will facilitate in vivo and histologic imaging studies to investigate models of osteoporosis, osteogenesis imperfecta, and osteonecrosis of the jaw, where drug-cell interactions leading to a positive or negative outcome have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…FRFP binding relies on local bone surface area, and removal of tracer probe is reflected in animals undergoing increased bone turnover. Combining fluorescent bisphosphonates with other fluorescent markers of osteoblastic, (72) osteocytic, (73) or osteoclastic (71) markers will facilitate in vivo and histologic imaging studies to investigate models of osteoporosis, osteogenesis imperfecta, and osteonecrosis of the jaw, where drug-cell interactions leading to a positive or negative outcome have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, expression of osteocytic markers coincides with mineralized nodule formation (41). We therefore examined expression of osteocyte-specific genes in calvarial osteoblasts cultured under osteogenic conditions, and found that after only 1 week in culture, expression of the osteocyte-specific genes Dmp1 and Phex was upregulated in mutant calvarial osteoblasts, coincident with the early appearance of mineralization ( Figure 6H).…”
Section: Deletion Of G S α In Osteoprogenitors Leads To Profound Ostementioning
confidence: 96%
“…The tissue dynamics of cartilage and bone accretion, removal and displacement during skeletogenesis remain undocumented. However, with the development of new time-lapse imaging approaches that reveal a dynamic process of cartilage and bone accretion, skeletogenesis is expected to depend on a highly dynamic mesenchymal tissue (Dallas and Veno, 2012;Dallas et al, 2009;Kamel-ElSayed et al, 2015).…”
Section: Limb Development and Skeletogenesismentioning
confidence: 99%